La vegetación del Concejo de Somiedo : su integración en una base de datos territorial - Garcia-Manteca P.; González Y.; Alvarez M.A.; Marquez J.; Fernández Prieto J.A. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
A vegetation map was prepared using 32 different types of vegetation elements as part of an environmental study of Somiedo area (Asturias). This information was digitised in one hectare elements to incorporate it in a territorial database. This database also contains topographic, geological and socioeconomic information. The combination of these files is able to provide new thematic maps, directly applicable to rural land use planning and resource management in this area.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)